2020
DOI: 10.28945/4668
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Using Virtual Experiments on Students’ Learning in the General Physics Lab

Abstract: Aim/Purpose: The objective of this study is to explore the effectiveness of using virtual experiments on students’ level of achievement and on their practical skills as well as their views on applying the virtual experiments in a general physics lab. Background: There is a continuous debate in the literature on the effect of using virtual experiments/ lab on students’ physics learning and whether those virtual experiments can substitute and/or enhance students’ performance in the real lab. Also, there is a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 9 publications
1
17
0
1
Order By: Relevance
“…These findings also supported the results from previous studies conducted [7], [19] regarding the contribution of multimedia to improving learning in the field of science. This research also was in line with research that succeeded in improving engineering-physics learning outcomes through multimedia modules [9], [22] and research that substantiated the superiority of multimedia with animation and simulation in learning science and technology [24]. The advantages of multimedia in the teaching and learning process in improving student achievement also are determined by the structure of their content preparation that takes into account design principles [16] and is in accordance with cognitive theory in line with students' thinking [17].…”
Section: Fig 3 Mean Scores Of Pretest and Posttestsupporting
confidence: 85%
See 1 more Smart Citation
“…These findings also supported the results from previous studies conducted [7], [19] regarding the contribution of multimedia to improving learning in the field of science. This research also was in line with research that succeeded in improving engineering-physics learning outcomes through multimedia modules [9], [22] and research that substantiated the superiority of multimedia with animation and simulation in learning science and technology [24]. The advantages of multimedia in the teaching and learning process in improving student achievement also are determined by the structure of their content preparation that takes into account design principles [16] and is in accordance with cognitive theory in line with students' thinking [17].…”
Section: Fig 3 Mean Scores Of Pretest and Posttestsupporting
confidence: 85%
“…A number of studies have discussed the teaching and learning of physics and basic engineering and their relation to study competence. Learning media based on augmented reality and virtual reality have proven to be quite influential in improving students' learning outcomes in various fields of expertise, such as physics [8], [22] and geoeducation [23], [24]. Research results also have proven the increasing effectiveness and efficiency of learning using learning media in the fields of science, technology, engineering, and mathematics [25], [26] and imagineering processes [27].…”
Section: Introductionmentioning
confidence: 99%
“…It indicated that the student can learn easily on how to use the BITADA kit. Hence, students' understanding can be improved using the BITADA kit [10]. The BITADA kit also has high usability level for the satisfaction aspect (M = 4.73, SD = 0.337).…”
Section: Usability Of the Bitada Kitmentioning
confidence: 99%
“…However, most experiments could not be performed during the home-based teaching and learning session due to the lack of scientific apparatus at home. Hence, the simulation can be utilized to replace the implementation of the experiment since it was proven to have a similar effect on students' understanding as experiments [10][11]. Thus, the simulation can be included in the teaching aids for the online home-based teaching and learning session.…”
Section: Introductionmentioning
confidence: 99%